Extended Follow-Up of Botensilimab Plus Balstilimab in an Expanded Cohort of Microsatellite-Stable Metastatic Colorectal Cancer Without Active Liver Metastases - Benjamin L. Schlechter; Marwan G. Fakih; Apostolia M. Tsimberidou; Andrea J. Bullock; Agustin Pimentel; Sunil Sharma; Heinz-Josef Lenz; Michael S. Gordon; Ghassan K. Abou-Alfa; Thomas U. Marron; Robert W. Lentz; Wells Messersmith; et al. (Clinical Cancer Research, 2026)
Abstract Purpose: Microsatellite-stable metastatic colorectal cancer (MSS mCRC) has limited treatment options and responds poorly to conventional immunotherapy. We report extended follow-up results from a fully-enrolled, phase 1b cohort evaluating botensilimab (BOT; Fc-enhanced anti–CTLA-4) plus balstilimab (BAL; anti–PD-1) in patients with MSS mCRC and no active liver metastases (NLM). Patients and Methods: Patients received BOT 1 or 2 mg/kg every 6 weeks (Q6W) plus BAL 3 mg/kg Q2W up to 2 years or until progression or unacceptable toxicity. Primary objective was safety/tolerability. Efficacy endpoints included objective response rate (ORR), duration of response (DOR), and progression-free survival (PFS); overall survival (OS) was exploratory. Patients with prior regorafenib, trifluridine/tipiracil±bevacizumab, or fruquintinib (“late-line exposed”) were analyzed post hoc. Results: As of December-13-2025, 123 patients were treated (median follow-up, 20.2 months [range, 0.7–62.3]). Median prior lines was 3 (range, 1–10; 67% had ≥3 prior lines). Most common treatment-related adverse events were diarrhea (39%; grade ≥3, 8%) and fatigue (37%; grade ≥3, 2%). ORR was 21% (95% CI, 14–29). Median DOR was not reached (NR; 95% CI, 7.3–NR), median PFS was 4.0 months (95% CI, 2.8–4.1), and median OS was 21.2 months (95% CI, 16.2–23.8; 36-month OS, 33% [95% CI, 24–43]). Efficacy was consistent in late-line–exposed patients (n=37; ORR, 22% [95% CI, 10–38]; median OS, 16.2 months [95% CI, 9.7–31.3]). Conclusions: BOT+BAL demonstrated durable responses, long-term survival, and manageable safety in previously-treated MSS mCRC NLM, including in late-line–exposed patients. These results support further evaluation.